A foundation of ecology rediscovered: 100 years of succession on the William S. Cooper plots in Glacier Bay, Alaska. Issue 6 (June 2017) - Buma, Brian; Bisbing, Sarah; Krapek, John; Wright, Glenn
Abstract: Understanding plant community succession is one of the original pursuits of ecology, forming some of the earliest theoretical frameworks in the field. Much of this was built on the long‐term research of William S. Cooper, who established a permanent plot network in Glacier Bay, Alaska, in 1916. This study now represents the longest‐running primary succession plot network in the world. Permanent plots are useful for their ability to follow mechanistic change through time without assumptions inherent in space‐for‐time (chronosequence) designs. After 100‐yr, these plots show surprising variety in species composition, soil characteristics (carbon, nitrogen, depth), and percent cover, attributable to variation in initial vegetation establishment first noted by Cooper in the 1916–1923 time period, partially driven by dispersal limitations. There has been almost a complete community composition replacement over the century and general species richness increase, but the effective number of species has declined significantly due to dominance of Salix species which established 100‐yr prior (the only remaining species from the original cohort). Where Salix dominates, there is no establishment of "later" successional species like Picea . Plots nearer the entrance to Glacier Bay, and thus closer to potential seed sources after the most recent glaciation, have had consistently higher species richness for 100 yr. Age of plots is the best predictor of soil N content and C:N ratio, though plots still dominated by Salix had lower overall N; soil accumulation was more associated with dominant species. This highlights the importance of contingency and dispersal in community development. The 100‐yr record of these plots, including species composition, spatial relationships, cover, and observed interactions between species provides a powerful view of long‐term primary succession.